2011
DOI: 10.1017/s0952675711000133
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of faithfulness in child-specific phonology

Abstract: This paper provides new evidence and analysis of gradual and U-shaped phonological learning. Using a rich longitudinal corpus from Trevor (Compton & Streeter 1977, Pater 1997b we demonstrate that some of Trevor's consonant harmony follows a statistically significant U-shaped trajectory, in contrast to the more typical S-shaped progression of his complex onsets. We then analyse these two developmental paths using an OT model of phonological acquisition (Hayes , in which the learner's variation within and across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…In general, it was observed that the phonological acquisition occurred in an ascending way, though with some regressions, as observed in other studies 12,13 . Most regressions occurred in consonants such as /´/, /l/ and /r/ in complex onset and coda.…”
supporting
confidence: 84%
“…In general, it was observed that the phonological acquisition occurred in an ascending way, though with some regressions, as observed in other studies 12,13 . Most regressions occurred in consonants such as /´/, /l/ and /r/ in complex onset and coda.…”
supporting
confidence: 84%
“…These patterns bear some resemblance with well-established facts about cross-linguistic preferences and empirical observations about phonological development. The CV sequence that is generally left intact in our participants' responses is also the most preferred cross-linguistically (Clements, 1990;Clements & Keyser, 1983) and the earliest to appear developmentally (e.g., Becker & Tessier, 2011;Goad & Rose, 2004;Ohala, 1999;Pater, 2009;Salidis & Johson, 1997). Why do these differences arise across syllable components?…”
Section: Concluding Comments On Syllable Organizationmentioning
confidence: 80%
“…Moreover, a preference for labial‐initial syllables is attested in child speech in various languages (e.g., MacNeilage and Davis ) and appears to have a biomechanically preferred status in general (Tsuji, Gomez, Medina, Nazzi, and Mazuka ). For additional discussion of constraint induction reflecting child‐specific phonetic pressures, see Inkelas and Rose () and Becker and Tessier ().…”
Section: Emergentism In Phonological Acquisitionmentioning
confidence: 99%
“…A final piece of evidence supporting the grammatical status of child speech patterns comes from the robustly documented phenomenon of U-shaped trajectories in phonological development (e.g., Leopold 1939;Leopold 1947;Ferguson and Farwell 1975;MacWhinney 1978;Bowerman 1982;Fikkert 1994;Bernhardt and Stemberger 1998;Rose 2007, 2003;Becker and Tessier 2011;Rose and Brittain 2011;McAllister Byun, 2012). In U-shaped learning, a child is observed to produce a speech target with relatively high accuracy early in development, then shift to a pattern of incorrect production that may be sustained for some time before accuracy again increases.…”
Section: Motor Pressures In Child Speech Patternsmentioning
confidence: 99%